ANALISIS HAMBATAN SAMPING TERHADAP KINERJA LALU LINTAS - Adhitya Eka Putra; Adris Ade Putra; Rini Sriyani (PRODI D3 TEKNIK SIPIL, 2016)
Abstract Kendari was road one of the roads is pretty solid, this is caused beecause the road were the lowliest market where a lot of the public who Transact buy and sell around the standards Development, with areas such as this much community activity that occurs on the side of the road, such as pedestrians, vehicle parking, slow vehiclesand vehicle exit/entrance on the side of the road.This research was conducted on the Development road of future fish auction market city of kendari. The data were taken, the situation is the primary data such as the geometric conditions of the road, traffic volume and speed, and the factors of the side barriers around the site of the research. While secondary data are population and location map.Based on the results of analysis and discussion, the highest side barriers on the Development road of Kendari is with frequency weighting Genesis 1365.1 the value entered into the classroom side barriers are very high (VH). The obstacles the side effect on traffic flow, reduced speed, reduced volume and high density. Influence of barriers against capacity can be seen from the decline in capacity without any obstacles the side of 2759.7 units of passenger cars/hour and with a side barrier into 2513.8 units of passenger cars/hour. the results of calculations for the degree of saturation, i.e. 0.26 Development Roads because of the results of the analysis below from 0.75 then no need to do planning, based on the degree of saturation level of service standards for the city of Kendari Enter category